PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP SIKAP EMPATI SISWA - Riza Sukma Fauzi; Didik (Universitas Majalengka, 2022)
The low interaction that occurs due to technological changes tends to be individualistic and results in empathy. Low empathy can lead to various deviant behaviors that need to be trained and familiarized with group learning. This research was conducted at MI PUI Tenajar Lor 2 school with the sample selected using two stage random sampling, with experimental design pre test post test control group design method, then an empathy questionnaire was used to measure students' empathy. The results showed that there was a difference in influence between the experimental group with the jingsaw type cooperative method and the control group with the conventional method, thus as an alternative to developing students' empathy, the jingsaw type cooperative method could be used. However, further research is needed to complete this research